Ω-soft sets and medical decision-making application. Issue 4 (3rd April 2021) - Kirişci, Murat
Abstract : Pythagorean Fuzzy Set is a generalization of the Intuitionistic Fuzzy Set. Therefore, in real-life problems for uncertainty, the decision-making mechanism in Pythagorean Fuzzy Sets outcomes better than Intuitionistic Fuzzy Set decision-making. For undefined objects, Soft Set is a new approach. Pythagorean Fuzzy Soft Set is deriving with the combination of Pythagorean Fuzzy Set and Soft Set. In this work, we will define the Pythagorean Fuzzy Parametrized Pythagorean Fuzzy Soft Set(Ω-Soft Set) and investigate some properties of the new set. The domain of the parameter function given in the new definition is a complete lattice. Selecting the domain of the Ω as a complete lattice allows us to solve some problems in the definitions and operations of the subset, union, and intersection. Besides, for Ω-Soft Set and other related concepts, we will present the decision-making problem solution as an application.